Parks and recreation system planning : a new approach for creating sustainable, resilient communities - Barth, David L. (Washington, D.C : Island Press, 2020)
Parks and recreation systems have evolved in remarkable ways over the past two decades. No longer just playgrounds and ballfields, parks and open spaces have become recognized as essential green infrastructure with the potential to contribute to community resiliency and sustainability. To capitalize on this potential, the parks and recreation system planning process must evolve as well. In Parks and Recreation System Planning, David Barth draws on real-world examples to provide a step-by-step approach to creating parks systems that generate greater economic, social, and environmental benefits. Chapters outline each step-evaluating existing systems, implementing a carefully crafted plan, and more-necessary for creating a successful, adaptable system.
Acknowledgements -- Introduction: A Framework for community Sustainability and Resiliency -- I. Generating Multiple Benefits -- II. Planning a comprehensive approach -- III. Executing the New Approach -- Appendixes -- Notes -- Index.
Includes index.
Keywords: PARKS PLANNING